IMPLEMENTASI NILAI-NILAI PENDIDIKA KARAKTER DALAM KITAB TA’LIMUL MUTA’ALLIM STUDI DI MADRASAH DINIYYAH AL-RIFA’IE PONDOK MODERN AL-RIFA’IE MALANG - Ilfikrotut Tamiya; Muhammad Hanief; Kukuh Santoso (VICRATINA, 2022)
The Modern Guide of Al-Rifa'ie is one of the modern, modern-based pesantren whose vision is to print broad-knowledge, artful and noble saints. In the Modern Guidelines Al-figure’ie santri is taught constantly to respect teachers and parents. At Al Rifa'ie santri's modern hut was also taught to do all kinds of everyday life activities by holding on to the Islamic holy guiding. In fact, there have been applications of daily life activities that fall within the conscriptable hut ordinance for sanitation. And who is violating the rules established by the hut, would receive the punishment or commonly known as ta’zir by the Modern Pondoc, Al-Rifa'ie. Not all of the santri also implemented what was already a hut rule. And of course it falls into the category of character crisis in the Modern guide Al-Rifa'ie style. In such a condition, the effort to plant the values of educational character in the generation of national successors, especially in the Modern Pondoc's sandbox Al-Rifa'ie, is a must. Because education has a vital role in building the character and intelligence of the nation's children to make for a better generation. Because of that, educational implementation must be continuously built and developed in order for the results of educational implementation to produce quality generation.